(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background. The aetiology of intussusception is unknown for most of the cases studied, although some associated conditions have been identified. We aimed to clarify the role played by enteric pathogens as potential risk factors for intussusception. Methods. A retrospective review of the records relating to hospitalizations for gastroenteritis with or without concurrent intussusception in Italian children was conducted among children aged <6 years old during the period 2005-2012. Through a multivariate logistic regression model, the associations, expressed as odds ratios with 95% confidence intervals, were estimated between the presence of gastroenteritis with intussusception and the explanatory variables, such as sex, age, the aetiology of gastroenteritis and whether the subjects lived in the North, South and Islands or Centre Italy. Results. A total of 174 records related to admissions due to the concomitant manifestation of gastroenteritis and intussusception were extracted and analyzed. The estimate of the adjusted odds ratio confirmed the significant contribution that sex and geographical location made to hospitalizations both for gastroenteritis with concurrent intussusception, and in the associated secondary diagnosis of gastroenteritis, with the exception of the rotavirus, where a different seasonality and a bucking trend were observed. The probability of intussusception became statistically significant lower from 12 months of age to ≤23 months and for age 48-59 months, respect to the first year of life. Conclusions. Our observational study highlighted males, affected by enteric infections, other than rotavirus and parasitic, living in North and Centre of Italy have an increased risk of developing intussusceptions. In the second and fifth year of life the probability of intussusceptions becomes lower than in the first year. Additional research is needed to confirm these findings and evaluate the pathogenesis which may link such infections with intussusception.